Mirror for the Other: Marijuana, Multivocality and the Media in an Eastern Caribbean Country - Rubenstein, Hymie (Anthropologica, 2022)
Cultural anthropology’s "Mirror for Man" has always been a mirror mainly by and for the West. A corollary of the preoccupation with writing to ourselves about the Other in the specialized jargon and prose of the discipline is that little effort is made by First World anthropologists to write for and to the Third World Other in a manner that is accessible to them. My aim is to illustrate how the discipline’s mandate of cultural critique can be extended to incorporate and engage that Other by referring to my experience of anthropology as journalism in the Eastern Caribbean country of St. Vincent and the Grenadines where my critique consisted of a long series of newspaper articles questioning elite and middle-class societal beliefs about the causes and consequences of marijuana production, sale and consumption.